Pre-screening IBD patients starting biologic therapies, a positive single centre quality improvement project. (21st January 2022) - Colclough, J; Ali, M; Shami, N; Aitchison, L; Hurst, A; Shams-Khan, H
Abstract: Background: Biologic therapies have revolutionised the management of IBD however their use can be associated with opportunistic infections and malignancy. BSG guidance 1 outlines the necessary pre-screening investigations required before starting these treatments. We assessed our compliance with these guidelines before and after implementing a proforma led SOP to evaluate whether there was any improvement in clinical practice. Methods: A pre-screening checklist proforma was created for all IBD patients starting biologic therapies at Southport and Ormskirk hospital and compliance with BSG guidelines was measured before and after its implementation. Data was collected retrospectively using electronic patient records over two 12-month cycles; pre-implementation (Nov 2018 – Oct 2019) and post-implementation (Feb 2020 – Jan 2021). Results: 31 patients (42% female, median age 48, range 19–84) were started on biologics before the checklist was implemented and 25 after (40% female, median age 40, range 17–73). Compliance with screening tests for baseline bloods and infections improved from 58.1% to 100%, with the largest improvements in Hep B and TB. S ee figure 1. Checking patient's vaccination history improved from 0% to 88% and adequate cervical screening improved from 3.2% to 66.7%. Overall, 80% of patients met full BSG pre-screening guidelines following implementation of the proforma, compared to 0% prior to this. Conclusion: The use of a pre-screening checklist has drastically improved the pre-screening process from 0% compliance to 88%, therefore improving patient safety prior to starting biologic therapies. This data compares favourably with national audit data where only 60% of patients had adequate pre-screening 2 . It has allowed us to standardise care to screen for contraindications to treatment, especially opportunistic infections. There is still room for improvement when assessing patients' vaccination and cervical screening histories, however these rely on documentation of the discussion in notes and may underestimate the number of patients receiving this advice. Overall we have shown a dramatic improvement in the quality of our care and therefore patient safety. We will continue to use the checklist as well as educating staff within the hospital about the importance of pre-screening before starting patients on biologic therapies. References: 1. Lamb CA, et al. British Society of Gastroenterology consensus guidelines on the management of inflammatory bowel disease in adults. Gut 2019;68:s1-s106. 2. Arnott I, et al. 2016. National clinical audit of biological therapies . Royal College of Physicians. https://www.rcplondon.ac.uk/projects/outputs/national-clinical-audit-biological-therapies-annual-report-2016 .